2009
DOI: 10.1126/science.1173275
|View full text |Cite
|
Sign up to set email alerts
|

An Expressed Fgf4 Retrogene Is Associated with Breed-Defining Chondrodysplasia in Domestic Dogs

Abstract: Retrotransposition of processed mRNAs is a frequent source of novel sequence acquired during the evolution of genomes. The vast majority of retroposed gene copies are inactive pseudogenes that rapidly acquire mutations that disrupt the reading frame, while precious few are conserved to become new genes. Utilizing a multi-breed association analysis in the domestic dog, we demonstrate that a recently acquired fgf4 retrogene causes chondrodysplasia, a short-legged phenotype that defines several common dog breeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
290
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(305 citation statements)
references
References 30 publications
7
290
0
2
Order By: Relevance
“…Basenji (10) Saluki ( identical mutation for foreshortened limbs (28). These mutations are unlikely to have arisen multiple times independently, implying a significant degree of gene flow between breeds.…”
Section: Resultsmentioning
confidence: 99%
“…Basenji (10) Saluki ( identical mutation for foreshortened limbs (28). These mutations are unlikely to have arisen multiple times independently, implying a significant degree of gene flow between breeds.…”
Section: Resultsmentioning
confidence: 99%
“…The functional importance of newly emerged genes have been increasingly recognized in last two decades, as a major contributor to adaptive evolution [10], such as human brain development [55], dog chondrodysplasia [19], mouse amyloid plaque resistance [56], and drosophila male-specific functions [12]. RNA-based retropositions have produced abundant retrocopies across mammalian genomes, hence presenting raw materials for evolution of novelties.…”
Section: Discussionmentioning
confidence: 99%
“…These newly formed retrocopies are normally non-functional (retropseudogenes) since they lack regulatory elements. However, a growing number of studies have demonstrated that retrocopies can evolve into functional genes (retrogenes) by acquiring regulatory elements through various ways [10][11][12][13] and have been shown to perform an important role in a range of species, including humans [14][15][16][17][18], mice [14], dogs [19,20], mosquitoes [21], and fruit flies [12,13,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the findings have been unexpected, such as the discovery that an additional fibroblast growth factor 4 (fgf4) gene introduced through retrotransposition is likely responsible for the short legs of many breeds including dachshunds and basset hounds (Parker et al 2009). The fact that all of the variation in dog coats (the length, texture, curliness, and patterns of hair) can be attributed to the combinatorial action of a mere three genes was another elegant demonstration of the power of applying genetic analyses to the traits most desired in purebreds.…”
Section: Doggedly Defining the Genetic Basis Of Diversitymentioning
confidence: 99%